Strategi Manajemen Risiko dalam Menangani Kerusakan Mobil Akibat Kelalaian Karyawan Bengkel - Sri Winarsih Ramadana (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2024)
The aim of this research is to determine risk management and compensation for car damage due to negligence of car repair shop employees in Peukan Baro District. The research method that the author uses is descriptive analysis with a qualitative approach. The research results show that risk management in dealing with car damage due to negligence of car repair shop employees in Peukan Baro District shows that the profit sharing system between the shop owner and employees, either 60% per 40% in Kana Mobil or 70% per 30% in Jasa Muda - is a practice general. Even if there is no written agreement, the employee's responsibility for car damage includes careful repair and maintenance. Disputes regarding damage are usually resolved through deliberation and written agreements to ensure clarity and prevent conflict. Workshop owners and employees are expected to have a clear agreement to avoid losses and ensure appropriate responsibilities in every situation.